Enhancing Green Underground Vlc Channels with Polar Codes and Multiresolution Analysis - Soto-Gomez, J; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2024)
This study aims to enhance the efficiency of Visible Light Communication (VLC) channels and contribute to the reduction of carbon emissions in underground communications by leveraging Polar Codes and Multiresolution Analysis (MRA). It uses a specific configuration of frozen bits for the implementation of Polar codes. Additionally, it integrates the Daubechies Wavelet family with a five-level decomposition into the MRA filters. The effectiveness of these methodologies is evaluated separately, without incorporating additional techniques into the communication channel. The results depicted a significant improvement, around of 19 dB in channel performance. This represent a considerable reduction in carbon emissions in a underground copper production context. © 2024 IEEE.
Keywords: VLC; Multiresolution Analysis; Polar Codes; Wavelet; Daubechies